KINERJA BANGUNAN BERTINGKAT DI KAWASAN PESISIR DALAM MENUNJANG KEMARITIMAN DAN PARIWISATA DI BANYUWANGI - M. Shofi'ul Amin; Mirza Ghulam; Dadang Dwi P; Erwin E (Politeknik Negeri Jakarta, 2020)
Banyuwangi is an area that belongs to zone 4 (SNI 03-1726-2002) and areas that are prone to earthquakes and are classified as moderate (SNI 03-1726-2012 and 2019). Other than, Banyuwangi also has the longest coastline on the island of Java, so buildings located in coastal areas have different air pressure that can cause very large winds to blow. So that in planning a building not only dead load and live load that needs to be planned but lateral loads also need to be planned. The survey results contained a tourism support building structure and are located very close to the coastal area of the Banyuwangi Dialoog Hotel. So the focus of this research is the construction of the structure. As for what is analyzed is the value of internal forces and deviations to the lateral loads of earthquake SNI 03-1726-2019 and wind loads based on PPIUG 1983 using the help of structural computer applications. The method used in earthquake load analysis is the spectrum response method. The results of the analysis of the value of the maximum force due to earthquake loads and wind loads are most influential on the column elements that cause inter-floor deviation. The deviation value is reviewed in the building service boundary performance, namely in the x and y directions respectively 10.89 mm and 15.75 mm. When viewed from the service threshold value of 87.5 mm, the structure is classified as safe from the influence of the lateral load of the planned earthquake and wind load. So that the building is feasible as a coastal building that is quite safe for commercial buildings and is able to become a tourist destination because it is so close to the sea. Keywords: Coastal, Lateral Load, Drift, Tourism.